Profitability of Supplementing Dried Distillers’ Grains Cubes to Improve Animal Performance and Replace N Fertilizer for Steers Grazing Introduced Pastures - Adams, Jordan (J Anim Sci, 2021)
During the summer grazing season, steers grazing introduced forages are oftentimes provided supplemental protein and energy to improve animal performance. However, it is important to determine if the additional supplementation is economically beneficial. Therefore, the objective was to evaluate the profitability of supplementing dried distillers’ grains cubes (DDGS) to improve animal performance or replace the use of N fertilizer (112 kg N/ha from urea) for steers (n = 149; BW = 238 ± 13.8 kg) grazing mixed tall fescue (Festuca arundinacea)/bermudagrass (Cynodon dactylon) pastures (n = 9 pastures, 7.2 ± 2.90 ha) from April 14 to September 17 (n = 155 d) using an enterprise budget analysis. Main plot supplemental treatments (n = 3 pastures/treatment) included 1) Fertilized Control (FC), no supplementation on fertilized pastures; 2) Fertilized Supplement (FS), 2.9 kg/steer DDGS supplemented 3-d/wk on fertilized pastures; and 3) Supplement (S), supplemental DDGS at 0.75% BW/d prorated for 5-d/wk feeding on unfertilized pastures. The assumptions used in this analysis were based on actual costs of inputs for pasture management and the DDGS offered, as well as the 5-year average Oklahoma auction market prices for 227 kg steers in April and 386 kg steers in October. Total cost per hectare was greater for S (P < 0.01), was least (P < 0.01) for FC, and FS was intermediate (P < 0.01). Cost per kg gain for FS and S was greater (P < 0.01) than for FC. Gross return per hectare tended to be greatest for S (P = 0.06), but net return per hectare was less for FS and S (P < 0.01) than FC. Although FS and S allowed for improvement of animal performance, our results imply that FC was the most profitable due to the cost of supplementation and low supplemental efficiency of S and FS. [Image: see text]